2022
DOI: 10.3389/fnut.2022.1036843
|View full text |Cite
|
Sign up to set email alerts
|

Application of 5-aminolevulinic acid promotes ripening and accumulation of primary and secondary metabolites in postharvest tomato fruit

Abstract: 5-Aminolevulinic acid (ALA) plays a vital role in promoting plant growth, enhancing stress resistance, and improving fruit yield and quality. In the present study, tomato fruits were harvested at mature green stage and sprayed with 200 mg L–1 ALA on fruit surface. During ripening, the estimation of primary and secondary metabolites, carotenoids, and chlorophyll contents, and the expression levels of key genes involved in their metabolism were carried out. The results showed that ALA significantly promoted caro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…Thus, coloration is a crucial step during fruit ripening and fruit postharvest storage. The transition of tomato fruit skin color is always conducted via the destruction of chlorophylls and the accumulations of new pigments, such as carotenoid, lycopene, and anthocyanins [ 27 ]. NO can postpone fruit coloration through judging pigment biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, coloration is a crucial step during fruit ripening and fruit postharvest storage. The transition of tomato fruit skin color is always conducted via the destruction of chlorophylls and the accumulations of new pigments, such as carotenoid, lycopene, and anthocyanins [ 27 ]. NO can postpone fruit coloration through judging pigment biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the impacts of GSNOR and NO on these nutrients may be different upon different treatment conditions and different storage periods. It has been found that phenolic acids and flavonoids are essential compounds for sustaining great quality in postharvest fruit [ 27 ]. Also, they are a crucial source for tomato flavor construction [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the juice of a tomato fruit was dropped on a digital refractometer PAL-1 (Atago, Tokyo, Japan) and the value of the soluble solids were measured [ 23 ]. The vitamin C content of the fruits was measured using the 2,6-dichloroindophenol staining method in conjunction with a spectrophotometric measurement at 500 nm [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…The detection wavelength was 210 nm, and the column temperature was 30 °C. The organic acid contents were determined according to the concentration curves of citric acid, malic acid, tartaric acid, fumaric acid, α-ketoglutaric acid, and oxalic acid standards [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Recently, natural amino acids have been widely applied in agricultural production as safe exogenous treatments. Exogenous amino acid treatment can regulate growth and development and can improve the quality of fruits and vegetables [ 7 ] and enhance the stress resistance of fruits [ 8 ].…”
Section: Introductionmentioning
confidence: 99%